2015
DOI: 10.1093/ilar/ilv004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Mouse Monopoly: Studying the Male Germ Line in Domestic Animal Models

Abstract: Spermatogonial stem cells (SSCs) are the foundation of spermatogenesis and essential to maintain the continuous production of spermatozoa after the onset of puberty in the male. The study of the male germ line is important for understanding the process of spermatogenesis, unravelling mechanisms of stemness maintenance, cell differentiation, and cell-to-cell interactions. The transplantation of SSCs can contribute to the preservation of the genome of valuable individuals in assisted reproduction programs. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 172 publications
1
45
0
Order By: Relevance
“…The targeting efficiency in primary germ cells achieved in the current study was similar to that reported for rodent SSCs (Chapman et al, 2015;Fanslow et al, 2014). (Gonzalez & Dobrinski, 2015).…”
Section: Targeted Mutagenesis In Spermatogoniasupporting
confidence: 88%
“…The targeting efficiency in primary germ cells achieved in the current study was similar to that reported for rodent SSCs (Chapman et al, 2015;Fanslow et al, 2014). (Gonzalez & Dobrinski, 2015).…”
Section: Targeted Mutagenesis In Spermatogoniasupporting
confidence: 88%
“…Sheep, mouse 3 Cleavage normalised on nIVC. 4 Blastocyst development normalised on ≥ 2-cell embryos. 5 Proportion of grade 1-2 blastocysts normalised on total number of blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…To create such sterile hosts, local testes irradiation has successfully depleted germ cells in sheep 2 and cattle 3 . However, this method requires general anaesthesia and access to expensive specialist equipment 4 . Depending on the radiation dose and animal's age at time of radiation, it may also leave some endogenous germ cells intact 2 , compromise testicular somatic cells [5][6][7] , slow down recovery of spermatogenesis and even reduce libido 7 .…”
Section: Introductionmentioning
confidence: 99%
“…As a proof of principle, our work has major implications for several types of studies in developmental biology. First, it provides the tools to investigate the dynamics of germ cell development in different species individually, which would benefit research of understudied mammalian species such as domesticated animals [35]. Furthermore, using the same experimental procedure in different species reduces noise and eliminates sources of variables that often challenge comparative studies.…”
Section: Discussionmentioning
confidence: 99%